Ответ:
x1 = -2
x2 = 1 - √2
x3 = 1 + √2
Объяснение:
x^3 - 2x^2 - x - 2 = 0
Воспользуемся формулой :
[tex](x - d)( {ax}^{2} + bx + c)[/tex]
[tex](x + 2)( {x}^{2} - 2x - 1) = 0[/tex]
x + 2 = 0
x = - 2 (первый корень)
[tex] {x}^{2} - 2x - 1 = 0[/tex]
Решаем через дискриминант.
D = b^2 - 4ac = (-2)^2 - 4 × 1 × (-1) = 4 + 4 = 8 > 0 , значит 2 корня.
[tex]x1 = \frac{2 - \sqrt{8} }{2 \times 1} = \frac{2 - 2 \sqrt{2} }{2} [/tex] = 1 - √2
x2 = (2 + 2√2) / 2 = 1 + √2
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
x1 = -2
x2 = 1 - √2
x3 = 1 + √2
Объяснение:
x^3 - 2x^2 - x - 2 = 0
Воспользуемся формулой :
[tex](x - d)( {ax}^{2} + bx + c)[/tex]
[tex](x + 2)( {x}^{2} - 2x - 1) = 0[/tex]
x + 2 = 0
x = - 2 (первый корень)
[tex] {x}^{2} - 2x - 1 = 0[/tex]
Решаем через дискриминант.
D = b^2 - 4ac = (-2)^2 - 4 × 1 × (-1) = 4 + 4 = 8 > 0 , значит 2 корня.
[tex]x1 = \frac{2 - \sqrt{8} }{2 \times 1} = \frac{2 - 2 \sqrt{2} }{2} [/tex] = 1 - √2
x2 = (2 + 2√2) / 2 = 1 + √2